2015
DOI: 10.1371/journal.pone.0134202
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Activation during Emotional Face Processing in Relation to Both Diagnosis and Polygenic Risk of Bipolar Disorder

Abstract: ObjectivesBipolar disorder (BD) is a highly heritable disorder with polygenic inheritance. Among the most consistent findings from functional magnetic imaging (fMRI) studies are limbic hyperactivation and dorsal hypoactivation. However, the relation between reported brain functional abnormalities and underlying genetic risk remains elusive. This is the first cross-sectional study applying a whole-brain explorative approach to investigate potential influence of BD case-control status and polygenic risk on brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Relatives had intermediate values that were not statistically different from that of either patients or controls. In line with previous reports (Whalley et al, 2012, Tesli et al, 2015), there was a significant effect of PGR-BD on task-related BOLD signal change independent of group but no significant PGR-BD score by group interactions. The current findings therefore support the notion that the polygenic load method is more informative in terms of identifying patterns of neural activation that mediate vulnerability to BD rather than symptom expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Relatives had intermediate values that were not statistically different from that of either patients or controls. In line with previous reports (Whalley et al, 2012, Tesli et al, 2015), there was a significant effect of PGR-BD on task-related BOLD signal change independent of group but no significant PGR-BD score by group interactions. The current findings therefore support the notion that the polygenic load method is more informative in terms of identifying patterns of neural activation that mediate vulnerability to BD rather than symptom expression.…”
Section: Discussionsupporting
confidence: 92%
“…The PGR score for BD (PGR-BD) is calculated in each individual by aggregating variation across GWAS loci nominally associated with BD into a quantitative score (International Schizophrenia Consortium et al, 2009, Dima and Breen, 2015), with the current PGR-BD explaining ~ 5% of the variance to BD (Cross-Disorder Group of the Psychiatric Genomics Consortium, 2013). Two previous studies have used the polygenic risk score method to examine the cumulative impact of BD-related risk-conferring SNPs on task-related brain activation during an emotional processing (Tesli et al, 2015) and a word generation task (Whalley et al, 2012). During emotional processing, a positive association was found in patients with BD and in controls between PRG-BD score and brain activation in the right vlPFC.…”
Section: Introductionmentioning
confidence: 99%
“…Meda et al[32] found that when compared to slow-5 ALFF, psychotic BD patients showed reduced regional power in the PCC in slow-4 band. Several task-based fMRI studies indicated reduced activation in the PCu/PCC in BD patients during the self-reflection task [33], emotional conflicts, and emotional faces matching tasks [34-36]. Structural MRI studies in BD patients revealed reduced gray matter and cortical thickness in the PCC [37-39].…”
Section: Discussionmentioning
confidence: 99%
“…A widely used and validated paradigm was employed to elicit amygdala activation. [24][25][26][27] In this task, participants selected which of two stimuli (displayed at the bottom of the screen) matched a target stimulus (displayed at the top). In the faces-matching task, the images displayed were human faces expressing either anger or fear ('negative faces'), or happiness ('positive faces').…”
Section: Experimental Paradigmmentioning
confidence: 99%
“…In the current study, we focused on participants' amygdala responses to negative stimuli (the negative faces>shapes contrast), because of the implication of altered threat-related facial affect perception in psychotic disorders 33,34 and since this contrast has been reported to reliably engage the amygdala. 27,35,36 Amygdala regions of interest (ROIs) were defined in accordance with the probabilistic Harvard-Oxford subcortical atlas provided with FSL, and were thresholded at 25% probability. Mean BOLD signal changes (parameter estimates) across all ROI voxels were extracted from FSL and used in statistical analyses.…”
Section: Fmri Data Analysismentioning
confidence: 99%